Respuesta :

Answer:

y = –1 + 3x

Step-by-step explanation:

To know which option is correct, we shall use the equation given in each option to see which will validate the table. This is illustrated below:

Option 1

y = –1x + 3

x = –2

y = –1(–2) + 3

y = 2 + 3

y = 5

This did not give the required value of y (i.e –7) in the table.

Option 2

y = 1 + 3x

x = –2

y = 1 + 3(–2)

y = 1 – 6

y = –5

This did not give the required value of y (i.e –7) in the table.

Option 3

y = –3 + 1x

x = –2

y = –3 + 1(–2)

y = –3 – 2

y = –5

This did not give the required value of y (i.e –7) in the table.

Option 4

y = –1 + 3x

x = –2

y = –1 + 3(–2)

y = –1 – 6

y = –7

This gives the required value of y (i.e –7) in the table.

Thus, the equation that matches the table is:

y = –1 + 3x

ACCESS MORE